1989
DOI: 10.1161/01.atv.9.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Test of effect of lipid lowering by diet on cardiovascular risk. The Minnesota Coronary Survey.

Abstract: The Minnesota Coronary Survey was a 4.5-year, open enrollment, single end-time, double-blind, randomized clinical trial that was conducted In six Minnesota state mental hospitals and one nursing home. It Involved 4393 Institutionalized men and 4664 Institutionalized women. The trial compared the effects of a 39% fat control diet (18% saturated fat, 5% polyunsaturated fat, 16% monounsaturated fat, 446 mg dietary cholesterol per day) with a 38% fat treatment diet (9% saturated fat, 15% polyunsaturated fat, 14% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
157
0
4

Year Published

1989
1989
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(162 citation statements)
references
References 4 publications
1
157
0
4
Order By: Relevance
“…CHD rates were reduced on the modified diet: 51% lower for CHD deaths alone (P = 0.10) and 67% lower for CHD deaths or major electrocardiogram change (P = 0.001). In a later US study of similar design, little evidence was seen for a reduction in CHD amongst the group with modified fat intake [27]; however, the mean follow-up of 1 year was likely too short to observe an effect.…”
Section: Trials Of Dietary Fat Modification For Prevention Of Chdmentioning
confidence: 92%
“…CHD rates were reduced on the modified diet: 51% lower for CHD deaths alone (P = 0.10) and 67% lower for CHD deaths or major electrocardiogram change (P = 0.001). In a later US study of similar design, little evidence was seen for a reduction in CHD amongst the group with modified fat intake [27]; however, the mean follow-up of 1 year was likely too short to observe an effect.…”
Section: Trials Of Dietary Fat Modification For Prevention Of Chdmentioning
confidence: 92%
“…8 Of 48 included randomised controlled trials in the other review, 24 were included in the current review. Of the remaining 24 randomised controlled trials, 10 did not compare reduced fat intake with usual fat intake (they were included as they modified fat), [53][54][55][56][57][58][59][60][61][62][63] and 13 aimed to reduce weight in some or all participants so were ineligible for the current review. [64][65][66][67][68][69][70][71][72][73][74][75][76] Only one trial was eligible for this review but was not included as no data were provided on body weight, body mass index, or waist circumference.…”
Section: Effects Of Reduced Fat Intake On Body Weightmentioning
confidence: 99%
“…Despite accumulating findings that suggest a relationship between saturated fat intake and CVD risk, a meta-analysis of 21 prospective cohort studies with 5-23 years of follow-up found no significant association between saturated fat intake and risk of stroke or CVD when the data were pooled together, even though individual studies had reported significant associations [42]. Similarly, no significant differences in the number and frequency of cardiovascular events and deaths between diets differing in fat composition were reported following periods of over 2 years [43]. It, therefore, remains unclear whether saturated fats are more dangerous in promoting CVD compared to unsaturated fats.…”
Section: Saturated Fatmentioning
confidence: 98%